Comparison of Ketamine, Fentanyl and Clonidine as an Adjuvant During Bupivacaine Caudal Anaesthesia in Paediatric Patients - Singh, Jeevan; Shah, RS; Vaidya, N; Mahato, PK; Shrestha, S; Shrestha, BL (Kathmandu University Medical Journal, 2013)
Background Caudal epidural analgesia with bupivacaine is very popular in paediatric anaesthesia for providing intra- and postoperative analgesia. Several adjuvants have been used to prolong the action of bupivacaine. Objectives To compare the efficacy of ketamine, fentanyl and clonidine in terms of quality and duration of analgesia they produce when added with caudal bupivacaine by single shot technique in children. Methods Eighty children, age one to ten years, undergoing sub-umbilical surgery, were prospectively randomized to one of four groups: caudal analgesia with 0.75 ml/kg of 0.25% bupivacaine in normal saline (Group B) or caudal analgesia with 0.75 ml/kg of 0.25% bupivacaine with 1 μg/kg of clonidine in normal saline (Group BC) or caudal analgesia with 0.75ml/kg of 0.25% bupivacaine with ketamine 0.5mg/kg (Group BK) or caudal analgesia with 0.75ml/kg of 0.25% bupivacaine with fentanyl 1mcg/kg (Group BF). Post-operative pain was assessed for 24 hours using the FLACC scale. Results The mean duration of analgesia was significantly longer in Group BC (629.06 ± 286.32 min) than other three groups P < 0.05. The pain score assessed using FLACC scale was compared between the four groups, and children in Group BC had lower pain scores, which was statistically significant. The requirement of rescue medicine was lesser in Group BC. Clonidine in a dose of 1 μg/kg added to 0.25% bupivacaine for caudal analgesia, during sub-umbilical surgeries, prolongs the duration of analgesia of bupivacaine, without any side effects in compare to fentanyl or ketamine. Conclusion We conclude that clonidine in a dose of 1 μg/kg, added to 0.25% bupivacaine for caudal analgesia and administered as a 0.75 ml/kg mixture in children, for sub-umbilical surgery, significantly prolongs the duration of post-operative analgesia when compared to 0.75 ml/kg of 0.25% bupivacaine in normal saline than 0.75 ml/kg of 0.25% bupivacaine with ketamine 0.5 mg/kg or 0.75 ml/kg of 0.25% bupivacaine with fentanyl 1 mcg/kg or 0.75 ml/kg of 0.25% bupivacaine alone, without any side effects. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 25-29 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8013